(untitled) (Research, Society and Development, 2023)
Hearing loss can be differentiated into three types, conductive, sensorineural or mixed, depending on the location of the auditory system where there is injury. The case report presented in this study addresses sensorineural hearing loss, which is defined as a decline in auditory sensitivity, in which the alteration is located in the cochlea or auditory nerve. Among the many causes that can affect these two areas are autoimmune diseases. The objective of this research is to report the case of an adolescent who presented a rapidly progressive sensorineural hearing loss, of probable autoimmune origin, describing the symptomatology, the evolution of the disease, the patient’s family history and analyzing the complementary exams performed by him. As well as reviewing the literature on the different etiologies and the bases of the diagnosis. This is a case study of an adolescent, who attended the care unit complaining of otalgia, headache and bilateral hypoacusis, with no alterations in the physical examination, evolving with progressive bilateral hypoacusis, with auditory exams compatible with sensorineural hearing loss. During the etiological investigation, the suspicion of systemic lupus erythematosus arose, due to the clinical history. Therefore, some exams were requested to confirm the origin of the hearing loss, however the patient did not return, making it impossible to continue the investigation. Early and accurate diagnosis is extremely important in cases of sensorineural hearing loss, mainly of autoimmune origin, as there is the possibility of regression and even remission of symptoms, if appropriate therapy is established.